Oxidation induced by dielectric barrier discharge (DBD) plasma treatment reduces IgG/IgE binding capacity and improves the functionality of glycinin. (30th November 2021) - Liu, Zhi-Wei; Zhou, Ying-Xue; Wang, Feng; Tan, Yi-Cheng; Cheng, Jun-Hu; Bekhit, Alaa El-Din; Aadil, Rana Muhammad; Liu, Xiu-Bin
Highlights: Reduction antigenicity of glycinin (91.64% for IgG and 81.49% for IgE) was obtained. Antigenicity elimination of glycinin was related to plasma-induced structural changes. An increase in the solubility from 10.78 ± 0.35% to 65.96 ± 1.86% was achieved. The emulsifying ability was increased from 21.08 ± 2.64 to 160.29 ± 4.12 m 2 /g. Abstract: The effect of dielectric barrier discharge (DBD) plasma treatment times from 2 to 5 min at 40 kV on IgG/IgE binding capacity and functionality of soybean glycinin was examined. A substantial reduction in the binding capacity (91.64% for IgG and 81.49% for IgE) was obtained after 5 min of plasma treatment, as determined by western-blot and ELISA analyses. Further studies demonstrated that the elimination of antigenicity and allergenicity of glycinin was directly related to plasma-induced structural changes on two aspects. A conformational alteration caused by oxidation of peptide bond amino groups, accompanied with an oxidation of Trp, Tyr, and Phe amino acid residues, which was confirmed by surface hydrophobicity, multi-spectroscopic analysis, and amino acid analysis. The cleavage of polypeptide chains inevitably partially diminished the linear epitopes, resulting in a primary decline in IgG/IgE binding capacity. Additionally, an increase in the solubility from 10.78 ± 0.35 to 65.96 ± 1.86% and significant increase in the emulsifying ability from 21.08 ± 2.64 to 160.29 ± 4.12 m 2 /g were observed after treatment of the plasma for 2 min. The present results confirm the potential use of DBD for the production of hypoallergenic soy protein-based products and improving their technical functions such as solubility and emulsifying ability.